Improving Students’ English Public Speaking Skill toward Campus Visit Program - Yudhie Indra Gunawan; Muhammad Daffa Haikal; Rafli Riansyah Riansyah; Daffa Andhika Rizky; Muhammad Nabhan Afrizal (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
The purpose of this study is to open the author's knowledge window directly, namely by conducting workshops so that UMT and UAD students can explore their public speaking in accordance with language cultures abroad and locally. not only that the workshop has a good impact, namely improving the quality and providing experience to students so that they can evaluate their English skills to speak in public, It is also useful in the context of globalization which will provide cross-cultural knowledge that is very important and valuable. In this paper, the author shares information about the Muhammadiyah museum and several tourist attractions and its history as learning material for a broader insight into an area.